Environmental service-learning in the United Arab Emirates: Is it mediated by the effects of biographical and demographical variables?. Issue 4 (2nd October 2019) - Howari, Fares; Qafisheh, Nida; Nazzal, Yousef
ABSTRACT: This study evaluates environmental service-learning in the United Arab Emirates (UAE) in relation to demographic variables and students' characteristics. A diverse group of school and community sites were recruited. Statistical analysis was performed between the final attitude index scores and demographic variables. UAE citizens were found to have a more positive attitude toward the environment than others. Educational level and age were also significantly associated with final attitude index scores. Participants aged 18–22 years scored significantly higher ( p < 0.003) than those who were younger than 18 years and older than 22 years.